Neonatal Intermittent Hypoxia Induces Lasting Sex-Specific Augmentation of Rat Microglial Cytokine Expression - Kiernan, Elizabeth A.; Wang, Tao; Vanderplow, Amanda M.; Cherukuri, Sneha; Cahill, Michael E.; Watters, Jyoti J. (Frontiers in Immunology, 2019)
1 Sleep disordered breathing (SDB) affects 3-5% of the pediatric population, including neonates who are highly susceptible due to an underdeveloped ventilatory control system, and REM-dominated sleep. Although pediatric SDB is associated with poor cognitive outcomes, very little research has focused on models of pediatric SDB, particularly in neonates. In adults and neonates, intermittent hypoxia (IH), a hallmark of SDB, recapitulates multiple physiological aspects of severe SDB, including neuronal apoptosis, sex-specific cognitive deficits, and neuroinflammation. Microglia, resident CNS immune cells, are important mediators of neurodevelopment and neuroinflammation, but to date, no studies have examined the molecular properties of microglia in the context of neonatal IH. Here, we tested the hypothesis that neonatal IH will enhance microglial inflammation and sex-specifically lead to long-term changes in working memory. To test this hypothesis, we exposed post-natal day (P1) neonates with dams to an established adult model of pathological IH consisting of 2 min cycles of 10.5% O2 followed by 21% O2, 8 hrs/day for 8 days. We then challenged the offspring with bacterial lipopolysaccharide (LPS) at P9 or at 6-8 weeks of age, and immunomagnetically isolated microglia for gene expression analyses and RNA-sequencing. We also characterized neonatal CNS myeloid cell populations by flow cytometry analyses. Lastly, we examined working memory performance using a Y-maze in the young adults. Contrary to our hypothesis, we found that neonatal IH acutely augmented basal levels of microglial anti-inflammatory cytokines, attenuated microglial responses to LPS, and sex-specifically altered CNS myeloid populations. We identified multiple sex differences in basal neonatal microglial expression of genes related to chemotaxis, cognition, and aging. Lastly, we found that basal, but not LPS-induced, anti-inflammatory cytokines were augmented sex-specifically in the young adults, and that there was a significant interaction between sex and IH on basal working memory. Our results support the idea that neonates may be able to adapt to IH exposures that are pathological in adults. Further, they suggest that male and female microglial responses to IH are sex-specific, and that these sex differences in basal microglial gene expression may contribute to sexual dimorphisms in vulnerability to IH-induced cognitive disruption.